S10.4a New mechanism and detection methods for azole-resistant Aspergillus fumigatus. (20th September 2022) - Watanabe, Akira; Arai, Teppei; Majima, Hidetaka
Abstract: S10.4 Emerging antifungal resistant fungi, September 24, 2022, 10:30 AM - 12:00 PM The most studied azole-resistant mechanism of Aspergillus fumigatus is decreased affinity of the drug for CYP51A, the drug target molecule, due to its amino acid substitutions. Typically, each azole-resistance caused by the designated amino acid substitution of CYP51A has a specific pattern depending on the substitution site. While uncovering non-cyp51A mechanisms responsible for azole resistance should be essential for developing novel methods for prompt diagnosis and effective drug treatment. In our previous study, we reported results that mutation of hmg1, which codes HMG-CoA reductase, the rate-limiting enzyme in ergosterol biosynthesis, would be the mechanism conferring azole-drugs resistance (EID 2018). On the other hand, different azole susceptibility patterns have been reported even among the strains possessing the same mutation in CYP51A. In this way, the overall picture of molecular mechanisms inducing azole resistance remains unclear. We performed a comparative genomic analysis among the strains with the same cyp51A mutation isolated from the same patient but with different azole resistance patterns. To investigate the association between the novel mutation and azole resistance, the mutant allele was replaced with the wild-type allele by the CRISPR-Cas9 system. Antifungal susceptibility tests were performed according to the CLSI-M38. As a result of genome comparison analysis between these two strains using the HiSeq sequencing system (Illumina), another mutation was found in the insulin-induced protein (INSIG) of the multiazole-resistant strain. The INSIG mutation contributes additively to azole resistance in collaboration with the CYP51A mutation but does not alone itself. We have already reported simple and rapid detection methods for A. fumigatus possessing CYP51A mutation using an endonuclease (AAC 2020). Furthermore, using MALDI-TOF-MS, we are developing a discriminant model to detect azole-resistant A. fumigatus.